The Valorisation of a City’s Public Spaces – A Case Study of Wieliczka - Serafin, Piotr (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
This article analyses the use of selected types of local public space - a market, museum areas (mines), parks, sacred spaces, and recreational spaces. The aim of the study was to estimate the value of aesthetic, historical, emotional, and highlighted market space and to identify spatial conflicts taking place in this environment, in one of Poland’s more well-known small cities - Wieliczka. This research confirms the lack of renown that small public spaces beyond the well-known mine have. Such spaces could give the city identity and serve to establish local community ties.